Hubungan Tingkat Pengetahuan dan Kualitas Hidup Terhadap Self Care Management pada Pasien Hipertensi di Puskesmas Cangkol Kota Cirebon Tahun 2022 - Like Efriani; Ismanurahman Hadi; Nur Aisyah (Universitas Borneo Lestari, 2023)
Self care management is the patient's activity in carrying out self care to improve the quality of life. Knowledge of hypertension is essential to control therapy and prevent complications. The higher the knowledge of hypertension, the better the self care management. The quality of life can affect hypertension, because it requires longterm treatment, giving rise to comorbidities so that it can lead to a decrease in the quality of life. This study aims to determine the relationship between knowledge level and quality of life on self care management in hypertensive patients. This research method uses observational with a cross-sectional approach. The sample in this study was 80 respondents and taken using a random sampling technique. The data were taken at the Cangkol Health Center in Cirebon City using a knowledge questionnaire (Hypertension Knowledge-Level Scale HK-LS), a quality of life questionnaire (WHOQOL-BREF) and a self care management questionnaire (HSMBQ) then analyzed using SPSS 25 with a Spearman correlation test. The results of the analysis showed that the most patients had a low level of knowledge (53%), the quality of life was very good (59%), self care management was sufficient (63%). The results of the spearman correlation test showed no relationship between knowledge level and self care management in hypertensive patients at the Cangkol Health Center in Cirebon City. with p value = 0.108 (p>0.005) and there is a relationship between quality of life and self care management in hypertensive patients at the Cangkol Health Center in Cirebon City in 2022 p value = 0.009 ((p<0.005).